Synthesis and Modified of Poly(Vinyl chloride) Contains Triazole Moieties and Studying the Optical Properties of New Polymers - Ahmed, Ahmed (Al-Nahrain Journal of Science, 2018)
New modified poly(vinyl chloride) was prepared by reacting of PVC with heterocyclic compounds that have thiole group (SH) in tetrahydrofuran as solvent. Heterocyclic compounds were characterized by FTIR,1H NMR spectroscopy and CHN analysis, while the new polymers have been characterized by FTIR spectrophotometers; the optical properties of synthesized new polymers were studied.